Rostrocaudal subregions of the ventral tegmental area are differentially impacted by chronic stress - Bambico, Francis Rodriguez; Li, Zhuoliang; Oliveira, Caio; McNeill, Sean; Diwan, Mustansir; Raymond, Roger; Nobrega, José N. (Psychopharmacology, 2019)
Rationale The ventral tegmental area (VTA) is implicated in the pathophysiology of depression and addictive disorders and is subject to the detrimental effects of stress. Chronic stress may differentially alter the activity pattern of its different subregions along the rostrocaudal and dorsoventral axes, which may relate to the variable behavioral sensitivity to stress mediated by these subregions. Objectives Here, chronic stress-exposed rats were tested for depressive-like reactivity. In situ hybridization for zif268 as a marker of neuronal activation was combined with in vivo single-unit recording of dopaminergic neurons to assess modifications in the activity of the rostral VTA (rVTA) and caudal VTA (cVTA). Changes in the expression of stress-responsive glucocorticoid receptors (GR) and brain-derived neurotrophic factor (BDNF) were also assessed. Results Stress-induced anhedonia-like, hyper-anxious, and passive-like responding were associated with reductions in dopaminergic burst activity in the cVTA and an increase in local GABAergic activity, particularly in GABA A receptor sensitivity. On the other hand, stress increased single-spiking activity, burst activity, and zif268 mRNA levels in the rVTA, which were associated with increased glutamatergic tonus and enhanced GR and AMPA receptor (AMPAR) expression. rVTA and cVTA activity differentially correlated with sucrose preference and passivity measures. Conclusions These data demonstrate that the rVTA and cVTA respond differently to stress and suggest that while cVTA activity may be related to passivity-like states, the activity of both subregions appears to be related to anhedonia and the processing of incentive value. These region-dependent abnormalities indicate the multi-modular composition of the VTA, which could provide multiple substrates for different symptom features.